Assembling and maintaining the Photosystem II complex in chloroplasts and cyanobacteria - Komenda, Josef; Sobotka, Roman; Nixon, Peter J (Current opinion in plant biology, 2012)
Plants, algae and cyanobacteria grow because of their ability to use sunlight to extract electrons from water. This vital reaction is catalysed by the Photosystem II (PSII) complex, a large multi-subunit pigment-protein complex embedded in the thylakoid membrane. Recent results show that assembly of PSII occurs in a step-wise fashion in defined regions of the membrane system, involves conserved auxiliary factors and is closely coupled to chlorophyll biosynthesis. PSII is also repaired following damage by light. FtsH proteases play an important role in selectively removing damaged proteins from the complex, both in chloroplasts and cyanobacteria, whilst undamaged subunits and pigments are recycled. The chloroplastic Deg proteases play a supplementary role in PSII repair.
Keywords: Photosystem II Protein Complex; biologické modely; Light; bakteriální proteiny; Bacterial Proteins; Models, Biological; fotosystém II (proteinový komplex); Photosynthesis; Plant Proteins; sinice; Cyanobacteria; světlo; rostliny; Plants; chloroplasty; rostlinné proteiny; Chloroplasts; fotosyntéza